Functional connectivity and characteristics of cortical brain networks of elderly individuals under different motor cognitive tasks based on functional near-infrared spectroscopy - Jiang, Shanshan; Qiu, Zhiqing; Cai, Xiaoqing; You, Tingting; Fu, Xinyu; Chen, Guanzhou; Li, Haoda; Ou, Haining (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study aimed to investigate age-related changes in brain functional connectivity during various motor and cognitive tasks, providing evidence for evaluating and intervening in brain aging.Methods15 elderly participants (ELD) and 30 young controls (YOU) were assessed. fNIRS haemodynamic responses were recorded during the Purdue nail board motor task, continuous minus 7 cognitive task, and motor-cognitive dual task. Differences in brain activation, functional connectivity, integral values, and barycentre values between the groups were compared using oxygenated haemoglobin (HbO) concentrations over time.ResultsThe ELD group performed significantly worse than the YOU group (p < 0.05). ELD participants showed significantly lower activation in the LSMA during motor tasks (p < 0.05), the RDLPFC and LDLPFC during cognitive tasks (p < 0.05), and both RSMA and LSMA during dual tasks (p < 0.05). Functional connectivity between LDLPFC, RSMA, LSMA, and RDLPFC–LDLPFC, LSMA–RSMA in the ELD group was significantly lower than in the YOU group (p < 0.05). The ELD group also had lower connectivity in RSMA, RDLPFC–LDLPFC, and LSMA–RSMA during cognitive tasks (p < 0.05). The centre of gravity for the ELD group was significantly lower during dual tasks compared to the YOU group (p < 0.05). In cognitive tasks, the ELD group showed significantly lower RSMA centre of gravity and integral values compared to dual tasks (p = 0.05).ConclusionElderly individuals exhibit lower cortical brain connectivity than young people across various tasks. fNIRS-based cerebral haemodynamics provide a useful quantitative measure for evaluating age-related brain changes.